2001
DOI: 10.1177/002215540104900311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Apoptotic Cells by Formamide-induced DNA Denaturation in Condensed Chromatin

Abstract: In this article we describe a novel effect of formamide on DNA of apoptotic nuclei and present a method for specific detection of apoptotic cells based on this effect. Our observations show that formamide induces DNA denaturation in apoptotic nuclei but has no such effect on DNA of non-apoptotic cells. Formamide-induced DNA denaturation combined with detection of denatured DNA with a monoclonal antibody (MAb) against single-stranded DNA made it possible to specifically identify the apoptotic cells. This proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
121
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 33 publications
7
121
1
1
Order By: Relevance
“…This conclusion is in disagreement with the data reported in several earlier studies (2)(3)(4)(5)(6)(7).…”
contrasting
confidence: 97%
See 4 more Smart Citations
“…This conclusion is in disagreement with the data reported in several earlier studies (2)(3)(4)(5)(6)(7).…”
contrasting
confidence: 97%
“…Under these conditions, the MAb detects DNA damage associated with apoptotic chromatin condensation per se, but does not detect presence of DNA breaks that require more intense denaturation (2,14). Electron microscopic studies confirmed this conclusion (6).…”
mentioning
confidence: 76%
See 3 more Smart Citations